New Insight into the Machined Surface Micro-roughness and the Tool Feed Relation - , Karol Vasilko, Zuzana Murčinková, Jozef Nosáľ (Archives of Current Research International, 2016)
The paper presents research results of analyzing the relation between the machined surface micro-roughness and tool feed f and thus introduces new insight into a problem comparing the experimental and theoretical results. During evaluation of profile records and theoretically defined rounded tool tip, the considerable disproportions can be found. In practice, this fact leads to incorrectly determination of tool feed for required value of Rz and selection of tool tip radius rɛ. The aim of the paper is to identify the reasons of such disproportions and suggest a method of their elimination by finding the more precise relation Rz-f as the standard well-known relation is. The many experiments were performed testing the low carbon steel machined by coated sintered carbide and ceramic tools.